2017
DOI: 10.1007/s00340-017-6820-x
|View full text |Cite
|
Sign up to set email alerts
|

The SPIRIT airborne instrument: a three-channel infrared absorption spectrometer with quantum cascade lasers for in situ atmospheric trace-gas measurements

Abstract: trace gases, enabling fast online and precise measurements with compact instrumentation. This technique has been implemented in aircraft [1,2], and is now more and more widespread. Most recently built airborne instruments comprise several variants, i.e., non-resonant cavities using tunable diode lasers (see, e.g., [3][4][5][6] and references therein), quantum cascade lasers (QCL; see, e.g., [7,8] and references therein), or difference frequency generation lasers [9], and resonant cavities for cavity ring-down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Dry volume mixing ratios (vmr) are deduced using the measured pressure and temperature of the optical cell and using the water vapour mixing ratios measured by a laser absorption spectroscopy hygrometer (WVSS-II from SpectraSensors). Total uncertainties for CO were estimated to be 4.7 ppb using comparisons performed during previous flights with high-altitude instrumented surface stations (Pic du Midi de Bigorre and Puy-de-Dôme, France) belonging to the WMO/GAW network and with a NOAA standard cylinder on board the aircraft (Catoire et al, 2017). They are also checked in the present campaign (see Sect.…”
Section: Airborne Payloadmentioning
confidence: 98%
See 1 more Smart Citation
“…Dry volume mixing ratios (vmr) are deduced using the measured pressure and temperature of the optical cell and using the water vapour mixing ratios measured by a laser absorption spectroscopy hygrometer (WVSS-II from SpectraSensors). Total uncertainties for CO were estimated to be 4.7 ppb using comparisons performed during previous flights with high-altitude instrumented surface stations (Pic du Midi de Bigorre and Puy-de-Dôme, France) belonging to the WMO/GAW network and with a NOAA standard cylinder on board the aircraft (Catoire et al, 2017). They are also checked in the present campaign (see Sect.…”
Section: Airborne Payloadmentioning
confidence: 98%
“…The SPIRIT airborne infrared absorption spectrometer for the measurements of trace gases was mounted on board the Falcon 20. A complete description of the instrument principle can be found in Catoire et al (2017). In brief, it uses continuous-wave distributed-feedback roomtemperature quantum cascade lasers (QCLs), allowing rapid scanning (each 1.6 s) of strong fundamental molecular rotational-vibrational lines lying in the mid-infrared, with ultra high spectral resolution (10 −3 cm −1 ).…”
Section: Airborne Payloadmentioning
confidence: 99%
“…The airborne CO and CH 4 measurements were performed with the SPIRIT instrument (Catoire et al, ), and CHBr 3 and CH 3 I with the GHOST instrument (Sala et al, ). Additionally, whole air samples taken in the RV Sonne were analysed for halocarbons, CO and CH 4 .…”
Section: Shiva Field Campaign and Measurementsmentioning
confidence: 99%
“…and C 2 H 6 providing best-in-class detection sensitivities of 40 ppt and 15 ppt, respectively. The custom-built airborne QCL spectrometer described by Catoire et al (2017) allows for simultaneous observation of CO, CH 4 and nitrogen dioxide (N O 2 ) with in-flight precisions of 0.3 ppb, 5 ppb and 0.3 ppb for a sampling time of 1.6 s. McManus et al (2011) reported on the development of a high-sensitivity trace gas instrument based on quantum cascade lasers and astigmatic Herriott cells with up to 240 m path length. This design is commercially available from AERODYNE RESEARCH INC., Billerica, USA, and allows for simultaneous observation of a multitude of gases, depending on the wavelength of the installed lasers.…”
Section: Introductionmentioning
confidence: 99%